Loss of cohesin complex components STAG2 or STAG3 confers resistance to BRAF inhibition in melanoma - Shen, Che-Hung (Nat Med, 2016)
The protein kinase V-Raf murine sarcoma viral oncogene homolog B (BRAF) is an oncogenic driver and therapeutic target in melanoma. Inhibitors of BRAF (BRAFi) have shown high response rates and extended survival in melanoma patients bearing tumors that express BRAF Val600 mutations, but a vast majority of these patients develop drug resistance. Here we show that loss of Stromal antigen 2 or 3 (STAG2 or STAG3), which encode subunits of the cohesin complex, in melanoma cells results in resistance to BRAFi. We identified loss-of-function mutations in STAG2 as well as decreased expression of STAG2 or STAG3 proteins in several tumor samples from patients with acquired resistance to BRAFi and in BRAFi-resistant melanoma cell lines. Knockdown of STAG2 or STAG3 decreased sensitivity of Val600Glu BRAF-mutant melanoma cells and xenograft tumors to BRAFi. Loss of STAG2 inhibited CCCTC-binding factor (CTCF)-mediated expression of dual specificity phosphatase 6 (DUSP6), leading to reactivation of ERK signaling. Our studies unveil a previously unknown genetic mechanism of BRAFi resistance and provide new insights into the tumor suppressor function of STAG2 and STAG3.